Present and future challenges to the church in Africa - with special reference to the church in Sudan - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Dissertation (MA (Science of Religion and Missiology))--University of Pretoria, 2006.